Ontogeny of sexual size dimorphism revisited: Females grow for a longer time and also faster - Sõber, Virve; Sandre, Siiri-Lii; Esperk, Toomas; Teder, Tiit; Tammaru, Toomas (PloS one, 2019)
Sex-specific mechanisms of the determination of insect body sizes are insufficiently understood. Here we use the common heath moth, Ematurga atomaria (Lepidoptera: Geometridae) to examine how larval growth trajectories differ between males and females. We monitored the development of 1379 larvae in controlled laboratory conditions. Sexually dimorphic development times during the first four instars were associated with sexual size dimorphism (SSD) in the beginning of the fifth (last) instar, when females were on average 15% heavier than males. Similarly, the duration of the last instar was about 13% longer in females. Further, we specifically focussed on the estimates of differential (instantaneous) growth rates of the larvae based on 24h mass increments of the 2nd, 3rd, 4th and 5th day in the beginning of the last instar. We calculated 'allometric' differential growth rates as the per-day increase in cube-root-transformed mass of the larvae. We found that allometric growth rates were slightly but significantly larger in females than in males. As this measure of growth rate (in contrast to the relative growth rate, based on the ratio of masses recorded at consecutive measurements) did not depend on body size, it allows an unambiguous separation of the effects of sex and size. We conclude that in accordance with an emerging general pattern, larger female body size in E. atomaria is achieved primarily by means of a longer growth period. Furthermore, our study shows that the differential growth rate can also be sexually dimorphic and contribute to SSD. This contribution, however, is lower than that of the development time by an order of magnitude. In addition to development periods and growth rates, other parameters of the non-linear growth curves of insect larvae also need to be considered in the context of SSD determination. In particular, weight loss prior to pupation was shown to be considerably larger in females than in males.
Keywords: časové faktory; Weight Loss; velikost těla; Moths; Time Factors; hmotnostní úbytek; Male; Larva; larva; Animals; Female; mužské pohlaví; ženské pohlaví; Body Size; pohlavní dimorfismus; Sex Characteristics; zvířata; můry